Diversity of Secondary Metabolism in Aspergillus nidulans Clinical Isolates - Claudio Greco (mSphere, 2020)
The filamentous fungus Aspergillus nidulans has been a primary workhorse used to understand fungal genetics. Much of this work has focused on elucidating the genetics of biosynthetic gene clusters (BGCs) and the secondary metabolites (SMs) they produce. SMs are both niche defining in fungi and of great economic importance to humans. Despite the focus on A. nidulans, very little is known about the natural diversity in secondary metabolism within this species. We determined the BGC content and looked for evolutionary patterns in BGCs from whole-genome sequences of two clinical isolates and the A4 reference genome of A. nidulans. Differences in BGC content were used to explain SM profiles determined using liquid chromatography–high-resolution mass spectrometry. We found that in addition to genetic variation of BGCs contained by all isolates, nine BGCs varied by presence/absence. We discovered the viridicatumtoxin BGC in A. nidulans and suggest that this BGC has undergone a horizontal gene transfer from the Aspergillus section Nigri lineage into Penicillium sometime after the sections Nigri and Nidulantes diverged. We identified the production of viridicatumtoxin and several other compounds previously not known to be produced by A. nidulans. One isolate showed a lack of sterigmatocystin production even though it contained an apparently intact sterigmatocystin BGC, raising questions about other genes and processes known to regulate this BGC. Altogether, our work uncovers a large degree of intraspecies diversity in BGC and SM production in this genetic model species and offers new avenues to understand the evolution and regulation of secondary metabolism.